2018
DOI: 10.1213/ane.0000000000002776
|View full text |Cite
|
Sign up to set email alerts
|

Chinese Anesthesiologists Have High Burnout and Low Job Satisfaction: A Cross-Sectional Survey

Abstract: The anesthesiologists in the Beijing-Tianjin-Hebei region of China expressed a below-average level of job satisfaction, and suffered a significant degree of burnout. Improvement in job satisfaction and burnout might create a positive work climate that could benefit both the quality of patient care and the profession of anesthesiology in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
88
1
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 76 publications
(99 citation statements)
references
References 27 publications
8
88
1
2
Order By: Relevance
“…A recent survey by the General Medical Council reported that 24% of trainees and 21% of trainers from across the United Kingdom (UK) described ‘feeling burnt out’ based on self-reported symptoms 9. The consequences of burnout among doctors have been investigated primarily in the United States (USA)10 with relatively few large studies conducted in Europe11–16 and Asia17 18 to validate these findings internationally. These include a negative impact on health including higher rates of substance abuse, depression, suicide and a poorer quality of life 19 20.…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey by the General Medical Council reported that 24% of trainees and 21% of trainers from across the United Kingdom (UK) described ‘feeling burnt out’ based on self-reported symptoms 9. The consequences of burnout among doctors have been investigated primarily in the United States (USA)10 with relatively few large studies conducted in Europe11–16 and Asia17 18 to validate these findings internationally. These include a negative impact on health including higher rates of substance abuse, depression, suicide and a poorer quality of life 19 20.…”
Section: Introductionmentioning
confidence: 99%
“…This observation contributes more to explain the feeling of discomfort in the caregiverpatient relationship often reported by patients attending public hospitals (11) and forebodes the poor professional temperament in public hospitals (14). However, the prevalence of burnout symptoms in Gabon's medical community is close to the values reported in the French, American (United States of America) and Asian medical settings (8,13,(15)(16)(17).…”
Section: Burnout Prevalencementioning
confidence: 83%
“…This observation contributes more to explain the feeling of discomfort in the caregiver-patient relationship often reported by patients attending public hospitals (12) and forebodes the poor professional temperament in public hospitals (15). However, the prevalence of burnout symptoms in Gabon's medical community is close to the values reported in the French, American (United States of America) and Asian medical settings (8,14,(16)(17)(18).…”
Section: Burnout Prevalencementioning
confidence: 84%